Quality Assurance in Islamic Education A Comparative Study of Accreditation Standards and Sharia Based Educational Values - Prasetio Utomo; Muhammad Irsyad Baitussalam (Lembaga Penerbitan, Penelitian, dan Pengabdian kepada Masyarakat (LP3M) of Institut Badri Mashduqi Probolinggo Jawa timur Indonesia, 2025)
Quality assurance in education is essential to ensuring accountability, transparency, and continuous improvement across institutions worldwide. In Islamic education, this process requires a dual focus: compliance with national and international accreditation standards and the preservation of Sharia-based values that emphasize ethics, spirituality, and holistic human development. This study employed a qualitative, comparative approach using document analysis, literature review, and thematic analysis to explore the intersection of accreditation requirements and Islamic educational principles. Findings reveal that quality assurance in Islamic education encompasses curriculum integrity, teaching and learning quality, governance, student development, and community engagement. Accreditation standards provide structure, accountability, and competitiveness, while Sharia values enrich education with moral and spiritual dimensions. The results show that both frameworks complement one another, fostering graduates who are academically competent and spiritually committed. However, challenges persist, including financial constraints, human resource limitations, and the difficulty of integrating secular and religious curricula. The study concludes that a balanced, integrated model of quality assurance rooted in both accreditation standards and Sharia principles offers a sustainable pathway for Islamic educational institutions, ensuring their credibility, integrity, and contribution to society.